Improving Entrepreneurial Satisfaction Through Creativity and Intellectual Agility-Resonance: Evidence from Indonesia - Roymon Panjaitan; Echan Adam; Muhammad Hasan (Gadjah Mada International Journal of Business, 2023)
Entrepreneurship is a personality attribute that enables a person to discover resources passionately through a combination of new strategies to generate significant market value. Therefore, this research aims to examine the importance of the intellectual agility-resonance of businesses in all industrial sectors in Indonesia. Quantitative data were collected from 303 small and medium-sized micro-enterprises and analyzed using SEM-PLS line analysis. The result showed that the intellectual agility-resonance of entrepreneurial creativity increases satisfaction. Furthermore, empirical research on aspects like psychological well-being, financial optimism, job risks, and outcomes show what can be achieved through intellectual agility-resonance. Theoretically, entrepreneurial creativity is an intellectuality that comes from the dimension of the source of competitive excellence.